Implementasi Metode MOORA Pada Seleksi Basiswa Kartu Indonesia Pintar Kuliah di Universitas Muhammadiyah Jember Berbasis Web - Rizky, Mohammad; Oktavianto, Hardian; Saifudin, Ilham (Puslitbang Akademi Relawan TIK Indonesia, 2025)
The Indonesia Smart Card Scholarship Program is a dedication of the government to the society, aimed at providing opportunities for all Indonesian citizens to obtain quality higher education without being hindered by economic factors. One of the educational institutions that accepts students receiving the KIP-College Scholarship is Muhammadiyah University Jember. In determining eligible students for the KIP-College scholarship, the Student Affairs Bureau still employs manual methods, making it difficult to perform complex data analysis and evaluate selection results. This research builds a Decision Support System to assist in the selection process for the KIP-College Scholarship at Muhammadiyah University Jember using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. This study utilizes several criteria with predetermined weights, namely, Decile Status, DTKS Status, Combined Parental Income, and Number of Dependents. The final result of this research is a ranking sorted from highest to lowest value, where the highest-ranking individuals are eligible to receive the KIP-College scholarship.